An investigation into mature adults' attitudinal reluctance to register as organ donors. Issue 10 (21st September 2016) - Quick, Brian L.; Reynolds‐Tylus, Tobias; Fico, Ashley E.; Feeley, Thomas Hugh
Abstract: Background: Mature adults (age 50–64) make up a large proportion of organ transplant recipients, and waiting list candidates yet are underrepresented in terms of actual donors. Understanding the reasons why mature adults fail to register as deceased organ donors is critical in achieving the goal of increasing the actionable supply of organs available for transplant. Conceptual models propose certain factors such as bodily integrity, ick (i.e., disgust), jinx (i.e., superstition), medical mistrust, salience, self‐efficacy, and stake are associated with organ donation registration attitudes. Moreover, the age myth, or the belief that one's age prevents them from becoming an organ donor, was examined among mature adults between the ages of 50–64. Method: An online survey was disseminated to mature adults (N=709). Results: Results indicated jinx, salience, self‐efficacy, and stake each predicted organ donation attitudes among mature adults. Moreover, results indicated that age myth accounted for attitudes toward registering as an organ donor among non‐registered mature adults after controlling for non‐cognitive and vested interest constructs. Conclusion: This study demonstrates the age myth is negatively associated with attitudes toward registering as organ donors. The results are discussed with an emphasis on both the theoretical and practical implications of study findings.